Bioremediation technology: A reliable and eco-friendly approach for the restoration of polluted environments - Mohammad Safari; Nasim Mosakhani; Ahmad Asl Hashemi; Gholamhossein Safari (آلودگی‌های محیطی و توسعه پایدار شهری)
Environmental pollution has escalated over the past few decades due to the rise in anthropogenic activities. Global industrialization and modern agricultural practices have led to the emergence of pollutants such as hydrocarbons, pesticides, and heavy metals. Bioremediation technology is a key strategy for addressing the diverse challenges posed by environmental pollution, leveraging the capabilities of microorganisms to clean and protect ecosystems and remove contaminants from polluted environments. Bioremediation is a process that involves the reduction, removal, modification, and transformation of pollutants in natural environments such as soil, sediments, air, and water using microorganisms, fungi, plants, or their enzymes in order to restore the damaged environment to its original conditions. Bioremediation technologies are broadly categorized into in-situ and ex-situ methods. In-situ bioremediation is dedicated to the treatment of pollutants at the contaminated site, while ex-situ bioremediation involves the collection and transfer of contaminated materials to another location for treatment. In-situ bioremediation methods include biosparging, bioventing, biostimulation, bioslurping, bioaugmentation, and phytoremediation. On the other hand, ex-situ methods include land farming, composting, biopiles, biofilters, bioreactors, and windrow methods. Despite the numerous advantages of this technology, such as sustainability, low cost, and environmental compatibility, bioremediation faces significant challenges including biological specificity, environmental variability, site heterogeneity, scalability issues, and regulatory barriers. Overcoming these obstacles requires interdisciplinary research, development, and management. This paper provides a comprehensive overview of bioremediation, its goals, principles, methods, influencing factors, benefits, and the challenges it faces, as well as future prospects for this technology, emphasizing the need for ongoing research to optimize and expand its applications.